PENGARUH KEYAKINAN DIRI DAN PENGETAHUAN AWAL TERHADAP MINAT BELAJAR MATERI AKUNTANSI KELAS XII SMA NEGERI DI KOTA MOJOKERTO - Istibsyaroh, Anis (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2013)
This correlational study investigates the effect of 1) self confidence on the students learning interest in Accounting, 2) prior knowledge on the students learning interest in Accounting, and 3) both self confidence and prior knowledge on the students learning interest in Accounting. Data were analyzed by using regression analysis, single tail t-test, and simultaneous F test. 345 of grade XII students of three senior high schools in Mojokerto (SMA Negeri 1, SMA Negeri 2 dan SMA Negeri 3) are the population of the study and 177 of them were taken as the sampled subjects using proportional random sampling technique. The finding shows that the operational t coefficient for self confidence is 9.708 (d.f.: 0.000) and the operational t coefficient for prior knowledge is 2.818 (d.f.: 0.005). In addition, the simultaneous F analysis yields in 58.047 (d.f.: 0.000). In conclusion, the higher the self confidence and prior knowledge the students have, the better their learning interest in Accounting will be. Similarly, these two variables simultaneously influence the learning interest in Accounting.